Jubilee in the Bible : using the theology of Jürgen Moltmann to find a new hermeneutic - Gunjevic, Lidija. (Biblical Interpretation Series, 2017)
The biblical message of Jubilee is becoming more credible in our days in dealing with the socio-economic and moral-spiritual issues of today's world. It continues to exercise a powerful influence on the religious thoughts and actions of God's people. In addition to that, this book reveals a new hermeneutical code of reading and interpreting the message of Jubilee. The synthesis of the exegetical analysis of the biblical texts regarding the Jubilee and Sabbath/Sabbath year and Moltmann's understanding of this subject reveals the meaning and significance of the topic, how it is recognized, as well as its implications in today's world. This synthesis reveals a new vision and starting point for socio-economic and moral-spiritual reform in our time. "The biblical Sabbat / Jubilee-traditions are much richer than we thought. This book shows it. Theologically often neglected they are a source of new ideas to solve problems of human community and the ecology of the earth. That my theological works can be used to apply them today, is a surprise to me, a happy surprise." Jürgen Moltmann